The effect of 4-way target passing training on increasing Gangga FC's passing accuracy in 2024 - galih sigaran (JOETAL: Journal of Education, Teaching and Learning, 2024)
Focus of the Research Problem Based on this, the author is interested in skills, there are still deficiencies in passing accuracy, therefore passing accuracy training is really needed for passing accuracy, they still use conventional and monotonous passing training models, players easily get bored in the training process. "The aim of the research is to find out the effect of 4-way target passing training on increasing Gangga FC's passing accuracy in 2024." The research design used in this research is a design using an experimental method. The research design is to use a one group pretest–posttest design. Overall sample of Gangga FC in 2024”. There are 22 sons. The sampling technique uses purposive sampling. From the results of the research and discussion, it can be concluded that: Based on the output results using SPSS 16, the average value of the results before being given the 4-direction passing training exercise was 7.3182 and after being given the training treatment was 9.1364, meaning that the average value had an effect on the 4-way passing training. The target direction for increasing Gangga FC's passing accuracy in 2024, there is a significant increase.